SOCIO-ECONOMIC CONTENT, CAUSES AND TYPES OF UNEMPLOYMENT - Pardayeva Ozoda; Rabimov Shohruh (Galaxy International Interdisciplinary Research Journal, 2023)
This article focuses on the socioeconomic substance, causes, and varieties of unemployment. The high degree of unemployment generates significant challenges in our country’s economy. The article investigates the primary causes of unemployment, its many expressions, and methods for eliminating them. State policies, national and international experiences, corporate development, and other essential measures have been widely applied in the fight against unemployment. One of the most essential strategies to alleviate the socioeconomic problems of unemployment is discussed in this article. Without studying unemployment issues, it is hard to completely comprehend the labor market and social-labor interactions. Unemployment is an unavoidable component of a free market economy.